Evaluasi Investasi dan Profitabilitas Pascapanen Lada Putih: Studi Kasus Efisiensi Manajemen Air Perendaman: Evaluation of Investment and Post-Harvest Profitability in White Pepper: A Case Study on the Efficiency of Soaking Water Management - Dicky Aditya Warman; Nur Rizqi Bariroh; Dhyani Nastiti Purwatiningdyah; Elfani Devitasari (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2026)
This study aimed to evaluate the investment feasibility and profitability of white pepper processing businesses through efficient soaking water management. A quantitative case study approach was employed at a white pepper processing enterprise in Kutai Kartanegara Regency, East Kalimantan, Indonesia. Financial feasibility was evaluated using Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP). The results indicated that all treatments generated positive NPV values, Net B/C ratios greater than one, IRRs exceeding the applied discount rate, and relatively short payback periods. The treatment without water replacement (P0) produced the highest financial performance among all treatments. Efficient soaking water management reduced operational costs while improving business profitability. These findings demonstrate that optimizing soaking water management not only enhances postharvest processing efficiency but also strengthens investment feasibility and supports the sustainable competitiveness of the white pepper agroindustry.